Learning from information technology: implication on curriculum of Islamic education - Syed Hassan, Sharifah Sariah (Institut Terjemahan dan Buku Malaysia, 2016)
With the advancement of technology, learning becomes easy but the explanation becomes complex. More complicated problems and real world scenarios have emerged that requires attention from the curriculum developers and educators. The curriculum be it Islamic Education or empirical knowledge such as science subjects cannot stay stagnant and need to be revisited. We no longer teach the way our teachers used to teach us. We always complain that our children do not like to read books or engage in recreational readings. We may assume that the reading habits are not inculcated since young. There is also the reason of time for reading has been replaced with watching television, engaging with computers and hand phone. The present trend of learning among adolescents prefer speed to accuracy, learning by doing rather than being told, rely on peers rather than their teachers in terms of worth paying attention to and more multitasking, able to do many things at one time (Trna & Trnova, 2013). Everything needs to be fast to ensure their interest is hooked. They prefer skimming and select their materials of reading rather than spending hours to read in something they have no interest in. They prefer to watch or listen to media and obtain the explanation rather to read on their own. Thus, their way of learning will no longer similar to our time. There is a danger of learning Islam from the media as our children are exposed to different perspectives and interpretations without knowing the authenticity of the contents and the authority of the presenter.